SOCIO-ECONOMIC PARTICULARITY AND CONSTRAINTS OF ARTISANAL FISHERFOLKS IN SELECTED FISHING COMMUNITIES ALONG KANJI DAM, NEW BUSSA, NIGER STATE - Omitoyin, S. A; Aderanti, O. R. (Nigerian Journal of Fisheries, 2018)
The study grappled with two important contending matters: the constraints of artisanal fishing in the Kanji dam area of Niger state and the connections between the demographic nature of respondents and their level of income. Data on Socio-economic features, fish species, gear used, and constraints were collected using a structured questionnaire. One Hundred (100) fisher folks were purposively selected from three fishing communities but 78 containing adequate information were retrieved. Analysis using descriptive and inferential statistics (Linear regression analysis) was carried out. The result showed male dominance (78.2%) and a mean age of 37.78±9.071. The major limitations faced by the fisher folks in the study area were low availability of credit with a mean score of 2.21, low access to modern fishing technology (2.13), corruption which include the use of unwholesome fishing gears and fishing practices (2.12). Absence of formal education (for the female gender) had a notable influence on the level of income at 1% while Postgraduate education, fishing experience, and household size had a notable influence on the level of income at 5%. Improving farmers’ access to cheap credit and mustering their savings to improve or enhance the constraints imposed by meagre finance, creating access to modern fishing technology use, putting systems in place to reduce corruption level as well as providing a joint cold storage facility in the communities should be encouraged.